Motivasi dan Harapan Mahasiswa Difable terhadap Pendidikan Inklusi UIN Sunan Kalijaga - Muryanti MA; Tri Mulyani (LP2M UIN Sunan Kalijaga, 2019)
Abstract Inclusion education gives an expectation to group of disabled people to get an equal education as the non-disabled people do. With this education, it is expected that they get the same opportunity to get jobs in order to become more prosper. This writing investigates how the motivation and the expectation of disabled people towards inclusion education which is held by UIN Sunan Kalijaga. The method used is qualitative and the primary data is obtained through observation and interview with disabled students. The secondary data is obtained from some documents owned by PLD UIN which is used to run this inclusion education. The result of investigation shows that most of disabled students have the same motivation as the nondisabled students to get education and pursue their dream. The learning process in UIN itself has not met their expectation because the lack of facilities and assistant, and lecturer who have not possessed proper skills and knowledge to teach disabled students.